TAFSIR MAQÄ€ÅžID DENGAN PENDEKATAN GENDER TERHADAP AYAT-AYAT HUKUM KELUARGA - Suqiyah Musyafaah (AL-HUKAMA, 2017)
This research focuses on rediscovering the verses about the establishment of the family law and the events or the reason of the revelation of the verses. It is then analyzed within the frame of maqÄÅŸid and gender approach. The verses can be classified into 3 areas, among others; (a) family law verses starting from marriage to separation either due to death or divorce, (b) the guardianship law verses of the immature child; (c) verses of family wealth law (amwÄl al-usrah) which includes inheritance, wasiyat, endowment and everything related to acceptance and or giving. The usage of maqÄÅŸid and gender perspectives are based on chapter al-RÅ«m (30): 21; that marriage rules are aimed to building a harmonious family, which spawns a loving relationship between husband and wife, and compassion among their children. The harmony is awakened through close relationship among husband, wife, and children who are able to fulfill their rights and obligations of each with full of love and affection. Each has the ability to control such rights and obligations freely and proportionately.